Active-Switched-Capacitor Based Diode Assisted and Capacitor Assisted Extended Switched Boost-Z-Source Inverters - Ahmad A.; Singh R.K. (My University, 2025)
This paper presents two novel topologies of active switched-capacitor based diode assisted and capacitor assisted extended single-phase Z-source inverter (ZSI) for high voltage gain. The boost factor of the classical ZSI/quasi-ZSI is limited because of the operating condition that summation of modulation index (M) and shoot-through duty cycle (D) is less than or equal to unity for simple boost control. Thus, to achieve higher voltage boost, a high value of D is required which leads to the lower operating value of M. Lower operating value of M leads to poor inversion operation at the fundamental power frequency with more total harmonic distortions, and finally, the performance of ac output gets degraded. The proposed topologies achieve high voltage gain with low D and give better inversion operation as compared to the existing high voltage gain inverters which are suitable for DC microgrid applications. The steady-state analysis of proposed inverters are discussed and verified with the simulation and experimental results. © 2018 IEEE.